Investigating the Role of Glutamate and GABA in the Modulation of Transthalamic Activity: A Combined fMRI-fMRS Study - Just, Nathalie; Sonnay, Sarah (Frontiers in Physiology, 2017)
The Excitatory-Inhibitory balance (EIB) between glutamatergic and GABAergic neurons is known to regulate the function of thalamocortical neurocircuits. The thalamus is known as an important relay for glutamatergic and GABAergic signals ascending/descending to/from the somatosensory cortex in rodents. However, new investigations attribute a larger role to thalamic nuclei as modulators of information processing within the cortex. In this study, functional Magnetic Resonance Spectroscopy (fMRS) was used to measure glutamate (Glu) and GABA associations with BOLD responses during activation of the thalamus to barrel cortex (S1BF) pathway at 9.4T. In line with previous studies in humans, resting GABA and Glu correlated negatively and positively respectively with BOLD responses in S1BF. Moreover, a significant negative correlation (R=-0.68, p=0.0024) between BOLD responses in the thalamus and the barrel cortex was found. Rats with low Glu levels and high resting GABA levels in S1BF demonstrated lower BOLD responses in S1BF and high amplitude BOLD responses in the thalamus themselves linked to the release of high GABA levels during stimulation. In addition, early analysis of resting state functional connectivity suggested EIB controlled thalamocortical neuronal synchrony. We propose that the presented approach may be useful for further characterization of diseases affecting thalamocortical neurotransmission.